Artificial Intelligence in Biological Cell Engineering: Future Directions and Transformative Potential - Singh, Jashanbir; Bhathal, Gurjit Singh (Journal of Research in Science and Engineering, 2026)
In the present paper an attempt has been made to Artificial, intelligence is growing quickly. The cybernetics was defined as a description of control and communication in living organisms and machines, by Norbert Wiener in 1948. Unfortunately, the part of living organisms is often underestimated. Recently, the initiative. A New Biology for the 21st Century of the US National Research Council of the National Academies, announced a goal of re - integration of the many sub - discipline of biology, and the integration into biology of physicists, chemists, computer scientists, engineers, and mathematicians to permit deeper understanding of biological systems. The similar aspect is expected to be a part of the next European framework Horizon 2020. Contemporary situation has to deal with two complementary issues: 1) The system theory and the artificial intelligence already produced plenty of theories, methods, and algorithms for processing and analysis of the digital (sampled and quantizied) signals, including images, to perform generous amount of possible results for given tasks. Various methods were gradually conditioned properly in specific or general way.2) On the other hand, biology (biochemistry, biophysics, systems biology) is able to generate troubling problems, which are mathematically analogous to the problems already solved in the other scientific fields. Thus, the interdisciplinary collaboration has a possibility to increase an impact of the joint solution.